Effect of Addition Percentage Zn on Mechanical Properties of Alloy Zn - Al - Ahmad Seng (ICETIA, 2016)
Aluminum is a light metal that has good corrosionresistance and good electrical conductivity.Aluminum usage is expected in the future still widelyopen both as the main material and supportingmaterials with the availability of aluminum seeds inthe abundant earth. By looking at the importance ofthe role of material selection in the advancement ofmanufacturing and assembling industry, the writerconsiders it necessary to conduct scientificpublication on alloy material with various laboratorytesting processes. The purpose of this research isconducting mechanical testing and metallographictesting on some type of percentage of Zinc-Aluminum material. The writer considers toconductalloying of Zinc-Aluminum using sandcasting technique with alloy composition: 1. Zn 25%- Al 75%, 2. Zn 50% - Al 50%., 3. Zn 75 % - Al25%. The method used in this study is to calculateand analyze the influence percentage of Zn additionto mechanical properties of aluminum-zinc alloys(Al-Zn). However, now its use is very widespreadeven it is difficult to describe how the developmentaviation industry without aluminum. Aluminum is ahighly stable oxide that cannot be reduced byreducing other metals. For aluminum-zinc alloys (Al75% - Zn 25%) it can be seen that the greater thestress value, the greater the strain value. This isinfluenced by the value of loading and extension thatoccur. For aluminum-zinc alloys (Al 50% - Zn 50%)it can be seen that the greater the stress value will befollowed by increasing the strain value, this isinfluenced by the loading and extension values thatoccur. For aluminum-zinc alloys (Al 25% - Zn75 %)it can be seen that the greater the stress valuefollowed by an increase in the value of strain, this isinfluenced by the value of loading and extension thatoccurred.